Multi-directional Cranial Distraction Osteogenesis for Treating Sagittal Synostosis with Frontometaphyseal Dysplasia: A Case Report. Issue 4 (23rd April 2021) - Morishita, Yuya; Sunaga, Ataru; Gomi, Akira; Hatade, Alice; Morita, Yuhei; Yoshimura, Kotaro
Abstract : Summary: Frontometaphyseal dysplasia (FMD), also known as Gorlin-Cohen syndrome, is a rare genetic syndrome. This syndrome affects the skeletal system and connective tissue, and causes a wide spectrum of manifestations of the skull, tubular bones, cardiovascular system, urinary system, and/or gastrointestinal system. Craniofacial findings of FMD are characterized by protruding supraorbital ridge, broad nasal bridge, hypertelorism, down-slanting palpebral fissures, and/or micrognathia. We describe a case of a 2-year-old girl diagnosed with sagittal synostosis accompanied with FMD. She presents anterior sagittal synostosis cranial form, compressed cerebrospinal fluid space (which suggested increased intracranial pressure), and the supraorbital hyperostosis. She underwent multi-directional cranial distraction osteogenesis in the calvaria and shaving of the supraorbital ridges. Despite concerns about bone fragility associated with FMD, the surgery was accomplished as usual. The patient had no intra- and postoperative complications. After 6 months of follow-up, the cranial shape has improved and the cerebrospinal fluid space has widened, but the supraorbital ridge has protruded again. Re-protrusion of the supraorbital ridge appears to be due to age-appropriate vigorous osteogenesis. The multi-directional cranial distraction osteogenesis procedure has been useful for treating sagittal synostosis even concomitant with FMD. Abstract : Supplemental Digital Content is available in the text.